UPAYA MENINGKATKAN AKTIVITAS BELAJAR MATEMATIKA MELALUI MODEL DISCOVERY LEARNING DENGAN THINK-PAIR-SHARE PADA SISWA KELAS VIII.I SMP N 3 KOTO BARU - Yeni Novitri (Ensiklopedia Education Review, 2020)
This is a Classroom Action Reserach in an attemp to improve students’ activity in learning Math subject of Grade VIII.1 SMPN 3 Koto Baru on the material of the samenes linear held from September to Desember 2014. The research is formulated in two cycles of twice classroom meetings for each cycle. Every cycle meeting drives four phases; planning, action,observation, and reflection. Instruments applied, are students’ activities observation sheets and questionaires. Analysis technique is Qualitative Descriptive and Percentage. The finding result of the reasearch in average is gained improvement to the students’ learning activity at every matter or each indicator from cycle one to cycle two; it is from 54% to 64%.